AgVO material with modified vanadium dioxide doped with silver ions, preparation method of AgVO material and application of AgVO material in aqueous zinc ion battery

By doping silver ions into VO2 material to form a silver vanadium oxide composite material, the problems of slow ion diffusion rate, poor stability and insufficient conductivity of VO2 material in aqueous zinc ion batteries are solved, and higher magnification capacity, cycle stability and electrochemical performance are achieved.

CN119852376APending Publication Date: 2025-04-18SHANGHAI UNIV OF ENG SCI
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510099497.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-18

Smart Images

  • Figure CN119852376A_ABST
    Figure CN119852376A_ABST
Patent Text Reader

Abstract

The invention discloses an AgVO material with modified vanadium dioxide doped with silver ions, a preparation method of the AgVO material and application of the AgVO material in an aqueous zinc ion battery. The silver ion doped modified vanadium dioxide AgVO material is prepared by the following steps: firstly, enabling vanadium pentoxide and anhydrous oxalic acid to react in water to obtain a clear dark blue solution; and then carrying out hydrothermal reaction on the dark blue solution and silver nitrate at 175-185 DEG C to obtain the silver vanadium oxide composite material with a nanofiber bundle microstructure, wherein the silver vanadium oxide composite material is formed by doping silver ions on the surface and inside of a VO2 material. The silver ion doped modified vanadium dioxide AgVO material provided by the invention has a nanofiber bundle microstructure, and an aqueous zinc ion battery taking the silver ion doped modified vanadium dioxide AgVO material as a positive electrode active material has excellent capacity, cycling stability and rate capability and excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silver ion-doped modified vanadium dioxide AgVO material and a preparation method thereof and application in an aqueous zinc ion battery, belonging to the technical field of aqueous zinc ion batteries. Background Art

[0002] In the context of climate change and energy crisis, energy supply shortages and price surges are serious, and energy transformation is imperative. Although clean energy such as wind, solar and ocean energy has great potential, they have intermittent and regional disadvantages due to factors such as geography, climate and time. Therefore, more advanced energy storage equipment needs to be developed to promote the development of new energy.

[0003] Lithium-ion batteries were once a commonly used energy storage device due to their light weight, high energy density, and long cycle life. However, intrinsic factors such as the scarcity of lithium resources, the high cost of lithium battery preparation, and high safety risks have made them gradually lack competitiveness. At present, aqueous zinc-ion batteries have become one of the most promising energy storage devices due to their extremely high safety, abundant surface Zn resources, eco-friendliness, high theoretical capacity (820 mAh / g), impressive long-term cycle stability, and superior rate capability. Aqueous zinc-ion batteries are usually composed of a positive electrode, a zinc negative electrode, an electrolyte, a separator, etc. The positive electrode material is the key factor that determines the performance of aqueous zinc-ion batteries.

[0004] VO2 material has a unique tunnel structure, which is conducive to the diffusion and embedding / ejection of zinc ions, and can alleviate the volume expansion effect caused by ion embedding, and has broad application prospects in the positive electrode of aqueous zinc-ion batteries. However, in actual tests, the ion diffusion rate in VO2 material is slow, the material stability is poor, and the conductivity of VO2 material itself is also insufficient. These all lead to insufficient rate capability and cycle capacity of batteries using VO2 material as positive electrode material, thus limiting the development of VO2 material in aqueous zinc-ion batteries. Summary of the invention

[0005] In view of the above problems existing in the prior art, the object of the present invention is to provide a silver ion doped modified vanadium dioxide AgVO material and a preparation method thereof and application in aqueous zinc ion batteries.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0007] A silver ion doped modified vanadium dioxide AgVO material is prepared by first reacting vanadium pentoxide and anhydrous oxalic acid in water to obtain a clear dark blue solution, and then hydrothermally reacting the dark blue solution with silver nitrate at 175-185°C to obtain a silver vanadium oxide composite material with a nanofiber bundle microstructure formed by doping silver ions on the surface and inside of the VO2 material.

[0008] A method for preparing AgVO material doped with silver ions and modified by vanadium dioxide comprises the following steps:

[0009] Vanadium pentoxide and anhydrous oxalic acid are dissolved in water, and then stirred at 60-70° C. to obtain a clear dark blue solution; then silver nitrate is added to the dark blue solution, and after the addition, it is stirred at room temperature for 5-15 minutes, and the obtained mixed solution is transferred to a reactor and subjected to hydrothermal reaction at 175-185° C. for 20-24 hours. After the reaction is completed, the solid product is collected to obtain the silver ion-doped modified vanadium dioxide AgVO material.

[0010] In one embodiment, the molar ratio of vanadium pentoxide: anhydrous oxalic acid: silver nitrate is 3: (6-12): (1-3).

[0011] In one embodiment, the operation of collecting the solid product is as follows:

[0012] After the reaction is completed, the reaction solution is cooled to room temperature and then centrifuged. The separated precipitates are washed with ethanol and deionized water respectively and then dried at 60-70° C. to constant weight to obtain the silver ion-doped modified vanadium dioxide AgVO material.

[0013] The invention discloses an application of a silver ion doped modified vanadium dioxide AgVO material in an aqueous zinc ion battery positive electrode, and the AgVO material is used as a positive electrode active material of the aqueous zinc ion battery positive electrode.

[0014] A method for preparing an aqueous zinc ion battery positive electrode comprises the following steps:

[0015] The AgVO material of silver ion doped modified vanadium dioxide is used as the positive electrode active material, the positive electrode active material, the conductive agent, the binder and the solvent are evenly mixed to form a positive electrode slurry, the obtained positive electrode slurry is coated on the surface of the positive electrode collector and then dried at 60-70° C. for 6-12 hours to obtain an aqueous zinc ion battery positive electrode.

[0016] In one implementation scheme, the conductive agent is acetylene black, the binder is polyvinylidene fluoride (PVDF), the solvent is N-methylpyrrolidone (NMP), the mass ratio of positive electrode active material: conductive agent: binder is 7:2:1; and the positive electrode current collector is a stainless steel mesh.

[0017] A water-based zinc ion battery comprises a positive electrode and a negative electrode, a separator arranged between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is the above-mentioned positive electrode of the water-based zinc ion battery, the negative electrode is zinc foil, the separator is glass fiber, and the electrolyte is a 3M Zn(CH3F3SO3)2 aqueous solution.

[0018] Compared with the prior art, the present invention has the following significant beneficial effects:

[0019] 1) The AgVO material of silver ion doped modified vanadium dioxide provided by the present invention is a silver vanadium oxide composite material with a nanofiber bundle microstructure formed by silver ions doped on the surface and inside of a VO2 material. The nanofiber bundle microstructure is conducive to full contact with the electrolyte and can effectively increase the diffusion rate of zinc ions. In addition, Ag doping can effectively enhance the structural stability of the VO2 material, enhance the reversibility of zinc ion embedding / ejection, and effectively enhance the pseudocapacitive effect of the VO2 material. When the AgVO material is used as the positive electrode of an aqueous zinc ion battery, the defects of the traditional VO2 material, such as slow ion diffusion rate, poor stability, and insufficient conductivity, can be effectively overcome.

[0020] 2) Aqueous zinc-ion batteries using silver ion-doped modified vanadium dioxide AgVO as the positive electrode active material at 0.5 A·g -1 At a current density of 1.34 W, the first cycle discharge capacity reached 359.9 mAh g -1 , at 3 A·g -1 After 500 cycles at a current density of 1.34 W, the discharge capacity still remained at 140.5 mAh g -1 , the capacity retention rate is 63.83%, with excellent capacity, cycle stability and rate performance, and excellent electrochemical performance;

[0021] 3) The preparation method of the present invention also has the advantages of simple operation and mild reaction conditions. Therefore, compared with the prior art, the present invention not only produces unexpected technical effects, but also has significant progress. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 SEM images of AgVO materials doped with silver ions and modified with vanadium dioxide prepared in Example 1, Example 2 and Example 3; wherein Figures (a), (b) and (c) correspond to AgVO-1-180, AgVO-2-180 and AgVO-3-180 materials prepared in Example 1, Example 2 and Example 3, respectively;

[0023] Figure 2 XRD patterns of AgVO materials doped with silver ions and modified with vanadium dioxide prepared in Example 1, Example 2 and Example 3;

[0024] Figure 3 The long cycle performance diagram of an aqueous zinc ion battery using the AgVO material prepared by silver ion doping modified vanadium dioxide in Example 1, Example 2 and Example 3 as the positive electrode active material;

[0025] Figure 4 The figure is a rate performance diagram of an aqueous zinc ion battery using the AgVO material prepared by silver ion doping modified vanadium dioxide in Example 1, Example 2 and Example 3 as the positive electrode active material;

[0026] Figure 5 The SEM images of the AgVO materials doped with silver ions and modified with vanadium dioxide prepared in Comparative Example 1, Comparative Example 2 and Example 3; wherein, Figures (a), (b) and (c) correspond to the AgVO-3-140, AgVO-3-160 and AgVO-3-180 materials prepared in Comparative Example 1, Comparative Example 2 and Example 3, respectively;

[0027] Figure 6 The graph is a cycle performance diagram of an aqueous zinc ion battery using the AgVO material of silver ion doped modified vanadium dioxide prepared in Comparative Example 1, Comparative Example 2 and Example 3 as the positive electrode active material;

[0028] Figure 7 This is a SEM image of the AgVO material doped with silver ions and modified with vanadium dioxide prepared in Comparative Example 3;

[0029] Figure 8 The graph is a cycle performance diagram of an aqueous zinc ion battery using the AgVO material prepared in Comparative Example 3 as the positive electrode active material;

[0030] Fig. 9 This is a SEM image of the AgVO material doped with silver ions and modified with vanadium dioxide prepared in Comparative Example 4;

[0031] Fig.10 This is a cycle performance diagram of an aqueous zinc ion battery using the AgVO material of silver ion-doped modified vanadium dioxide prepared in Comparative Example 4 as the positive electrode active material. DETAILED DESCRIPTION

[0032] The technical scheme of the present invention is further described in detail and completely below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.

[0033] Example 1

[0034] 1. Preparation of AgVO materials doped with silver ions and modified with vanadium dioxide

[0035] 3 mmol of vanadium pentoxide and 9 mmol of anhydrous oxalic acid were dissolved in 20 mL of water, and then stirred at 65°C for 2 hours to obtain a clear dark blue solution. Then, 1 mmol of silver nitrate was added to the dark blue solution. After the addition, the mixture was stirred at room temperature for 10 minutes. The obtained mixed solution was transferred to a reactor and subjected to hydrothermal reaction at 180°C for 24 hours. After the reaction, the reaction solution was cooled to room temperature and centrifuged. The separated precipitates were washed alternately with ethanol and deionized water for several times and then vacuum dried at 65°C to constant weight to obtain the silver ion-doped modified vanadium dioxide AgVO material, abbreviated as AgVO-1-180.

[0036] 2. Preparation of AgVO-1-180 aqueous zinc ion battery

[0037] The prepared AgVO-1-180 material is used as the positive electrode active material of the positive electrode of the aqueous zinc ion battery. The positive electrode active material: acetylene black: polyvinylidene fluoride are mixed in a mass ratio of 7:2:1 (the positive electrode active material, acetylene black and polyvinylidene fluoride can be fully mixed by shaking three times with a high-speed vibration stirrer), and then an appropriate amount of NMP is added. The mixture is stirred and ground to form a positive electrode slurry. The obtained positive electrode slurry is then coated on the surface of a stainless steel mesh and dried to obtain a positive electrode sheet of an aqueous zinc ion battery. The positive electrode sheet is cut into a circular positive electrode sheet with a diameter of 12 mm, and the cut positive electrode sheet is used as the positive electrode of the aqueous zinc ion battery. A zinc foil (purity of 99.9% and thickness of 2 mm) is used as a negative electrode, a glass fiber is used as a separator, and a 3M A Zn(CH3F3SO3)2 aqueous solution is used as the electrolyte, and a commercially available CR2032 battery shell is used as the battery shell (including a positive electrode shell and a negative electrode shell). A button-type aqueous zinc ion battery is assembled in the order of "positive electrode shell-positive electrode sheet-electrolyte-glass fiber separator-HPT / annealed zinc negative electrode sheet-gasket-spring-negative electrode shell" using the existing button battery assembly technology.

[0038] Example 2

[0039] The only difference between this embodiment and embodiment 1 is that in the preparation process of the silver ion doped modified vanadium dioxide AgVO material, the amount of silver nitrate added is 2 mmol, and the rest of the contents are the same as described in embodiment 1. The prepared silver ion doped modified vanadium dioxide AgVO material is abbreviated as AgVO-2-180.

[0040] Example 3

[0041] The only difference between this embodiment and embodiment 1 is that in the preparation process of the silver ion doped modified vanadium dioxide AgVO material, the amount of silver nitrate added is 3 mmol, and the rest of the contents are the same as described in embodiment 1. The prepared silver ion doped modified vanadium dioxide AgVO material is abbreviated as AgVO-3-180.

[0042] Figure 1 The SEM images of the AgVO materials doped with silver ions and modified with vanadium dioxide prepared in Example 1, Example 2 and Example 3 are shown in Figures (a), (b) and (c) respectively correspond to the AgVO-1-180, AgVO-2-180 and AgVO-3-180 materials prepared in Example 1, Example 2 and Example 3. It can be seen from the figure that the microstructures of the AgVO materials prepared in Example 1, Example 2 and Example 3 are all in the form of nano-scale fiber bundles, and with the increase of the amount of silver doping, the arrangement of the fiber bundles in the AgVO material becomes more and more regular and the distribution becomes more and more uniform. In addition, the fiber bundles are intertwined with each other, and there are certain gaps between the fibers in the fiber bundles. With the increase of the amount of silver doping, the gaps between the fibers in the fiber bundles become larger, which is more conducive to improving the surface area of ​​the AgVO material, so that the AgVO material can be fully in contact with the electrolyte after being applied to the zinc ion battery, thereby improving the Zn 2+ The embedding / extraction efficiency can effectively improve the stability of zinc-ion batteries, making them have excellent electrochemical properties.

[0043] Figure 2 XRD patterns of AgVO materials doped with silver ions and modified vanadium dioxide prepared in Example 1, Example 2 and Example 3; as can be seen from the figure, AgVO-1-180, AgVO-2-180 and AgVO-3-180 materials prepared in Example 1, Example 2 and Example 3 all contain a structure similar to VO2, and the incorporation of Ag does not significantly change the crystal structure of the VO2 material. In addition, no other impurity peaks exist in the XRD pattern of the AgVO material, indicating that the AgVO material has a good degree of crystallization. In addition, it can be seen from the XRD pattern that at a lower angle (38.2°), there is a diffraction peak corresponding to the (111) crystal plane, indicating that Ag is successfully incorporated, thereby proving that the AgVO material is successfully prepared.

[0044] The aqueous zinc ion battery using the silver ion doped modified vanadium dioxide AgVO material prepared in Example 1, Example 2 and Example 3 as the positive electrode active material was subjected to a long cycle test. During the test, the voltage range was set to 0.2-1.2V, and the battery was cycled 500 times at a current density of 3 A / g. The test results are as follows: Figure 3 shown.

[0045] Figure 3 The long cycle performance diagram of the aqueous zinc ion battery using the AgVO material doped with silver ions and modified vanadium dioxide prepared in Example 1, Example 2 and Example 3 as the positive electrode active material; it can be seen from the figure that at 3A·g –1In the long cycle at a current density of , after 500 cycles, the specific capacity of the AgVO-1-180 aqueous zinc ion battery of Example 1 increased from 170.31 mAh·g -1 Down to 63.75mAh·g -1 The capacity retention rate is 37.43%, and the specific capacity of the AgVO-2-180 aqueous zinc ion battery of Example 2 is increased from 220.27 mAh·g -1 Down to 82.42 mAh g -1 The capacity retention rate is 37.43%. The specific capacity of the AgVO-3-180 aqueous zinc ion battery in Example 3 is increased from 220.1 mAh·g -1 Down to 140.5 mAh g -1 , the capacity retention rate is 63.83%; it can be seen that the AgVO materials prepared in Examples 1-3 have high stability, and the aqueous zinc ion batteries using the AgVO materials prepared in Examples 1-3 can maintain high discharge specific capacity in short and long cycles, and have good cycle stability. The AgVO-3-180 aqueous zinc ion battery of Example 3 has the best cycle stability, indicating that the doping amount of Ag in the AgVO material has a certain influence on the stability of the prepared AgVO material and the corresponding zinc ion battery.

[0046] The rate performance of aqueous zinc ion batteries using AgVO materials doped with silver ions and modified vanadium dioxide prepared in Example 1, Example 2 and Example 3 as positive electrode active materials was tested. During the test, the voltage range was set to 0.2-1.2 V, and 5 cycles were performed at current densities of 1, 3, 4, 6, 8, and 10 A / g, respectively. The test results are shown in FIG. Figure 4 shown.

[0047] Figure 4The figure is a rate performance diagram of an aqueous zinc ion battery using the AgVO material doped with silver ions and modified vanadium dioxide prepared in Example 1, Example 2 and Example 3 as the positive electrode active material; as can be seen from the figure, at a current density of 1, 3, 4, 6, 8, and 10 A / g, respectively, the average specific capacity of the AgVO-1-180 aqueous zinc ion battery of Example 1 is 179.38, 136.93, 115.02, 96.88, 77.77, 65.03, and 56.5 mAh / g, respectively; the average specific capacity of the AgVO-2-180 aqueous zinc ion battery of Example 2 is 221.84, 195.96, 180.86, 170.14, 154.63, 142.47, and 132.48 mAh / g, respectively; the average specific capacity of the AgVO-2-180 aqueous zinc ion battery of Example 2 is 221.84, 195.96, 180.86, 170.14, 154.63, 142.47, and 132.48 mAh / g, respectively; the average specific capacity of the AgVO-3 aqueous zinc ion battery of Example 3 is 142.30, 142.70, and 132.75 mAh / g, respectively. The average specific capacities of the aqueous zinc ion batteries using the AgVO materials prepared in Examples 1-3 are 260.2, 233.2, 211.9, 197.4, 181.0, 166.0, and 154.5 mAh / g, respectively. It can be seen that the aqueous zinc ion batteries using the AgVO materials prepared in Examples 1-3 all have good rate performance, and the rate performance of the AgVO-3-180 aqueous zinc ion battery in Example 3 is the best, indicating that the doping amount of Ag in the AgVO material has a certain influence on the rate performance of the prepared AgVO material and the corresponding zinc ion battery.

[0048] Comparative Example 1

[0049] The only difference between this embodiment and embodiment 3 is that during the preparation of the silver ion-doped modified vanadium dioxide AgVO material, the temperature of the hydrothermal reaction is 140° C., and the rest of the contents are the same as those described in embodiment 3. The prepared silver ion-doped modified vanadium dioxide AgVO material is abbreviated as AgVO-3-140.

[0050] Comparative Example 2

[0051] The only difference between this embodiment and embodiment 3 is that during the preparation of the silver ion-doped modified vanadium dioxide AgVO material, the temperature of the hydrothermal reaction is 160° C., and the rest of the contents are the same as those described in embodiment 3. The prepared silver ion-doped modified vanadium dioxide AgVO material is abbreviated as AgVO-3-160.

[0052] Figure 5The SEM images of the AgVO materials doped with silver ions and modified with vanadium dioxide prepared in Comparative Example 1, Comparative Example 2 and Example 3; wherein, Figures (a), (b) and (c) correspond to the AgVO-3-140, AgVO-3-160 and AgVO-3-180 materials prepared in Comparative Example 1, Comparative Example 2 and Example 3, respectively; it can be seen from the figure that in Comparative Example 1, during the hydrothermal reaction at 140°C, the reaction system is prone to agglomeration, and the obtained AgVO-3-140 material does not form obvious In terms of structural shape, the AgVO-3-160 material prepared by hydrothermal reaction at 160°C in Comparative Example 2 has a coexistence of rod-like structure and block-like structure, while the AgVO-3-180 material prepared by hydrothermal reaction at 180°C in Example 3 presents a nano-scale fiber bundle structure. The AgVO-3-180 material has a larger surface area than the AgVO-3-140 and AgVO-3-160 materials, and can fully contact with the electrolyte after being applied to zinc ion batteries, thereby improving the Zn 2+ The insertion / extraction efficiency gives zinc-ion batteries excellent electrochemical performance, which shows that the temperature of the hydrothermal reaction has a significant effect on the microstructure and electrochemical properties of the prepared AgVO material.

[0053] The aqueous zinc ion battery using the AgVO material doped with silver ions and modified vanadium dioxide prepared in Comparative Example 1, Comparative Example 2 and Example 3 as the positive electrode active material was subjected to a cycle test. During the test, the voltage range was set to 0.2-1.2 V, and the battery was cycled 50 times at a current density of 0.5 A / g. The test results are as follows: Figure 6 shown.

[0054] Figure 6 The cycle performance diagram of the aqueous zinc ion battery using the AgVO material doped with silver ions and modified vanadium dioxide prepared in Comparative Example 1, Comparative Example 2 and Example 3 as the positive electrode active material; it can be seen from the figure that after 50 cycles at a current density of 0.5 A / g, the specific capacity of the AgVO-3-140 aqueous zinc ion battery of Comparative Example 1 increased from 275.86 mAh·g -1 Down to 182.56 mAh g -1 The capacity retention rate is 66.18%, and the specific capacity of the AgVO-3-160 aqueous zinc ion battery in comparative example 2 is increased from 315.43 mAh·g -1 Down to 245.62mAh·g -1 The capacity retention rate is 77.87%. The specific capacity of the AgVO-3-180 aqueous zinc ion battery in Example 3 is increased from 358.75 mAh·g -1 Down to 298.34 mAh g -1, the capacity retention rate is 83.16%; it can be seen that under the same conditions, the aqueous zinc-ion battery using fiber-bundle AgVO-3-180 has better discharge specific capacity and cycle stability than the aqueous zinc-ion battery using AgVO-3-140 with no obvious structural shape and the aqueous zinc-ion battery using AgVO-3-160 with both rod-like structure and block structure, indicating that the microstructure of AgVO has a significant effect on the performance of the final aqueous zinc-ion battery.

[0055] Comparative Example 3

[0056] The only difference between this embodiment and embodiment 3 is that during the preparation of the silver ion-doped modified vanadium dioxide AgVO material, the temperature of the hydrothermal reaction is 200° C., and the rest of the contents are the same as those described in embodiment 3. The prepared silver ion-doped modified vanadium dioxide AgVO material is abbreviated as AgVO-3-200.

[0057] Figure 7 The SEM image of the AgVO material doped with silver ions and modified with vanadium dioxide prepared in Comparative Example 3 is shown; as can be seen from the figure, the AgVO-3-200 material prepared at a hydrothermal temperature of 200°C exhibits a chaotic block and rod-shaped interwoven structure. Combining Example 3 and Comparative Example 3, it can be seen that too high a hydrothermal temperature will cause the structure of AgVO to change from a uniform state to a chaotic state. Combining Example 3 and Comparative Examples 1-2, it can be seen that the temperature of the hydrothermal reaction has a significant effect on the microstructure of the prepared AgVO material. The hydrothermal reaction temperature cannot be too low or too high. The microstructure of the AgVO material prepared at a hydrothermal reaction temperature of 180°C is optimal.

[0058] The aqueous zinc ion battery using the AgVO material doped with silver ions and modified vanadium dioxide prepared in Comparative Example 3 as the positive electrode active material was subjected to a cycle test. During the test, the voltage range was set to 0.2-1.2 V, and the battery was cycled 50 times at a current density of 0.5 A / g. The test results are as follows: Figure 8 shown.

[0059] Figure 8 The cycle performance diagram of the aqueous zinc ion battery using the AgVO material of silver ion doped modified vanadium dioxide prepared in Comparative Example 3 as the positive electrode active material; it can be seen from the figure that after 50 cycles at a current density of 0.5 A / g, the specific capacity of the AgVO-3-200 aqueous zinc ion battery of Comparative Example 3 is increased from 270.40 mAh·g -1 Down to 162.45 mAh g -1, the capacity retention rate is 60.08%. Compared with the AgVO-3-180 material of Example 3, the discharge specific capacity and cycle stability are significantly reduced. Combining Example 3 and Comparative Examples 1-2, it can be seen that the temperature of the hydrothermal reaction has a significant effect on the electrochemical properties of the prepared AgVO material. The hydrothermal reaction temperature cannot be too low or too high. The electrochemical performance of the AgVO material prepared by the hydrothermal reaction at 180°C is the best.

[0060] Comparative Example 4

[0061] The only difference between this embodiment and embodiment 1 is that in the preparation process of the silver ion doped modified vanadium dioxide AgVO material, the amount of silver nitrate added is 4 mmol, and the rest of the contents are the same as described in embodiment 1. The prepared silver ion doped modified vanadium dioxide AgVO material is abbreviated as AgVO-4-180.

[0062] Fig. 9 The SEM image of the AgVO material doped with silver ions and modified with vanadium dioxide prepared in Comparative Example 4 is shown. It can be seen from the figure that when the amount of silver nitrate added is 4 mmol, the prepared AgVO-4-180 presents an irregular chaotic structure. Combining Example 3 and Comparative Example 4, it can be seen that too high a silver doping amount will cause the structure of the AgVO material to change from a regular state to an irregular state, which is not conducive to the penetration of the electrolyte. It can be seen that the silver doping amount has a significant effect on the microstructure of the prepared AgVO material.

[0063] The aqueous zinc ion battery using the AgVO material doped with silver ions and modified vanadium dioxide prepared in Comparative Example 3 as the positive electrode active material was subjected to a cycle test. During the test, the voltage range was set to 0.2-1.2 V, and the battery was cycled 50 times at a current density of 3 A / g. The test results are as follows: Fig.10 shown.

[0064] Fig.10 The cycle performance diagram of the aqueous zinc ion battery using the AgVO material modified with silver ion doped vanadium dioxide prepared in Comparative Example 4 as the positive electrode active material; it can be seen from the figure that after 50 cycles at a current density of 3 A / g, the specific capacity of the AgVO-4-180 aqueous zinc ion battery of Comparative Example 4 increases from 219.48 mAh·g -1 Down to 89.9 mAh g -1 , the capacity retention rate is 40.96%; compared with the AgVO-3-180 material in Example 3, the cycle stability is significantly reduced. It can be seen that the silver doping amount has a significant effect on the electrochemical properties of the prepared AgVO material.

[0065] Finally, it should be pointed out that the above are only some preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above contents of the present invention all fall within the scope of protection of the present invention.

Claims

1. A silver ion doped modified vanadium dioxide AgVO material, characterized in that: The silver vanadium oxide composite material with a nanofiber bundle microstructure is obtained by first reacting vanadium pentoxide and anhydrous oxalic acid in water to obtain a clear dark blue solution, and then hydrothermally reacting the dark blue solution with silver nitrate at 175-185°C to obtain a silver vanadium oxide composite material with a nanofiber bundle microstructure formed by doping silver ions on the surface and inside of the VO2 material.

2. A method for preparing the silver ion-doped modified vanadium dioxide AgVO material according to claim 1, characterized in that: The steps include: Vanadium pentoxide and anhydrous oxalic acid are dissolved in water, and then stirred at 60-70° C. to obtain a clear dark blue solution; then silver nitrate is added to the dark blue solution, and after the addition, it is stirred at room temperature for 5-15 minutes, and the obtained mixed solution is transferred to a reactor and subjected to hydrothermal reaction at 175-185° C. for 20-24 hours. After the reaction is completed, the solid product is collected to obtain the silver ion-doped modified vanadium dioxide AgVO material.

3. The method for preparing the AgVO material doped with silver ions and modified with vanadium dioxide according to claim 2, characterized in that: The molar ratio of vanadium pentoxide: anhydrous oxalic acid: silver nitrate is 3: (6-12): (1-3).

4. An application of the silver ion doped modified vanadium dioxide AgVO material according to claim 1 in the positive electrode of an aqueous zinc ion battery, characterized in that: Used as positive electrode active material for aqueous zinc ion battery positive electrode.

5. A method for preparing a positive electrode for an aqueous zinc ion battery, characterized in that: The following operations are included: The AgVO material of silver ion doped modified vanadium dioxide as claimed in claim 1 is used as a positive electrode active material, the positive electrode active material, the conductive agent, the binder and the solvent are evenly mixed to form a positive electrode slurry, the obtained positive electrode slurry is coated on the surface of the positive electrode collector and then dried at 60 to 70° C. for 6 to 12 hours to obtain an aqueous zinc ion battery positive electrode.

6. The method for preparing an aqueous zinc ion battery positive electrode according to claim 5, wherein: The conductive agent is acetylene black, the binder is polyvinylidene fluoride, the solvent is N-methylpyrrolidone, and the mass ratio of the positive electrode active material: the conductive agent: the binder is 7:2:

1.

7. An aqueous zinc ion battery, characterized in that: It includes a positive electrode and a negative electrode, a separator arranged between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is the positive electrode of the aqueous zinc ion battery prepared according to claim 5, the negative electrode is zinc foil, the separator is glass fiber, and the electrolyte is a 3M Zn(CH3F3SO3)2 aqueous solution.

Citation Information

Cited By

  • Preparation method of silver vanadium oxide nanowire positive electrode material for zinc ion battery

    CN118062892A

  • Zeta-V2O5 material with tunnel structure as well as preparation method and application of zeta-V2O5 material

    CN121974398A